Editorial: Driving, cycling and flying: trends in planning and operational transportation research in Europe - Homem de Almeida Correia, Gonçalo; Santos, Bruno F.; Kroesen, Maarten (European Journal of Transport and Infrastructure Research, 2017)
In this special issue we present three papers selected from the 18th meeting of the EURO Working Group on Transportation (EWGT) which was held in July 2015 in Delft, the Netherlands, organized by Delft University of Technology. The selected contributions reflect the diversity of topics that were addressed in this conference, which is dedicated to mathematical modeling of transportation problems. We are happy to have a small but representative sample in which three different modes of transportation are in focus: the bicycle, the car and the airplane. The editors are very grateful for all the work that authors and referees have put in creating interesting research papers in this broad field of transportation research. This editorial first explains what the EWGT is and how the EWGT conference was organized. The three contributions are then presented and put into the perspective of the Dutch edition of the EWGT conference.